Need for Cardiovascular Risk Reduction in Persons With Serious Mental Illness: Design of a Comprehensive Intervention - Dalcin, Arlene T.; Jerome, Gerald J.; Appel, Lawrence J.; Dickerson, Faith B.; Wang, Nae-Yuh; Miller, Edgar R.; Young, Deborah R.; Charleston, Jeanne B.; Gennusa, Joseph V.; Goldsholl, Stacy; Heller, Ann; Evins, A. Eden; et al. (Frontiers in Psychiatry, 2019)
Persons with serious mental illness (SMI) comprise a high-risk group for cardiovascular disease (CVD)-related mortality with rates at least twice those of the overall US. Potentially modifiable CVD risk behaviors (tobacco smoking, obesity, physical inactivity, unhealthy diet) and risk factors (hypertension, diabetes, dyslipidemia) are all markedly elevated in persons with SMI. Evaluations of programs implementing integrated medical care into specialty mental health settings have not shown meaningful effects on CVD risk factor reduction. Rigorously tested, innovative interventions are needed to address the large burden of CVD risk in populations with SMI. In this article, we describe the design of a comprehensive 18-month intervention to decrease CVD risk that we are studying in a randomized clinical trial in a community mental health organization with psychiatric rehabilitation programs. The individual-level intervention incorporates health behavior coaching and care coordination/care management to address all seven CV risk behaviors and risk factors, and is delivered by a health coach and nurse. If successful, the intervention could be adopted within current integrated care models and significantly improve the physical health of persons with SMI.